2018
DOI: 10.9734/jeai/2017/38522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Thinning Season Using Metamitron on Peaches ‘Sensação’ Quality

Abstract: Aims: The objective of this study was to evaluate peach fruits quality after chemical thinning using metamitron at different times in the South of Brazil. Study Design: The experimental design was in randomized blocks, with five replications of three plants, fruits were harvested and evaluated the central plant in the plot, and twenty fruits were evaluated in each replicate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
2
5
0
1
Order By: Relevance
“…No direct relation could be established between periods of chemical thinning and peach pulp firmness, since physiological responses varied among crops. These results agree with Farias et al (2017), who observed that pulp firmness was affected between periods of application of metamitron to peach tree thinning and the crop. However, pulp firmness did not exhibit any differences after the application of metamitron to apple tree thinning in four different periods (Gabardo et al, 2017).…”
Section: Firmness Of the Pulpsupporting
confidence: 92%
See 4 more Smart Citations
“…No direct relation could be established between periods of chemical thinning and peach pulp firmness, since physiological responses varied among crops. These results agree with Farias et al (2017), who observed that pulp firmness was affected between periods of application of metamitron to peach tree thinning and the crop. However, pulp firmness did not exhibit any differences after the application of metamitron to apple tree thinning in four different periods (Gabardo et al, 2017).…”
Section: Firmness Of the Pulpsupporting
confidence: 92%
“…Therefore, the lower the ripening index, the less amount of chlorophyll (Andrade et al, 2015), due to pectin solubilization (Zhang et al, 2010;Pegoraro et al, 2015). Data collected by this study agree with the ones found by Farias et al (2017), who observed that the ripening index of peaches yielded by cultivars 'Sensação' was lower when plants were thinned manually and with metamitron on the 20th and 30th DAFB. However, when chemical thinning with metamitron was carried out on the 50th and 60th DAFB, peaches had higher RI values (Table 1).…”
Section: Ripening Indexsupporting
confidence: 88%
See 3 more Smart Citations